Reading the poker face representations of women in selected songs of Lady Gaga - Malazzab, Shiela Mae S. (College of Arts and Letters, University of the Philippines Diliman, 2012)
The aim of the study is to establish a connection between language used and ideology through the analysis of Lady Gaga's song lyrics. It aims to provide an understanding of how women are presented in the lyrics of Lady Gaga. In addition, it aims to look at how the images of women presented in Lady Gaga's song lyrics reflect her ideology and stance as a 'feminist'. The theory that is used in the study is the Speech Act Theory as proposed by Austin and Searle. In addition, it is supplemented by the postmodern feminism to evaluate if Lady Gaga is a feminist or not. The study uses two level of analysis to establish connections between Lady Gaga's language use and her feminist ideology. The surface level of analysis is based on the frequency of the occurrences of illocutionary acts in her lyrics. The deep level of analysis aims to look at the content of each speech act. The research findings show that the illocutionary acts with the most number of occurrences are assertives and directives. On the surface level, it shows an empowered image of a woman. However, on the deeper level, some lines show an image of disempowerment while some lines show an image of empowerment. The summary shows that eleven out of twelve songs analyzed in the study are inconsistent on the presentation of the woman's image. By inconsistency, it means either intra-text inconsistencies in which different images are presented in a song. Or it could mean inconsistency based on the difference between the postmodern feminist ideals and the image of the woman presented in each song. It is concluded that Lady Gaga can be considered a feminist if she is viewed in a postmodern feminist perspective. She presented an image of an empowered woman because woman are able to exercise her power to choose, power to assert beliefs, power to express her feeligs, and power to control the situation around her.